Pengaruh Media Audio Visual Terhadap Keterampilan Menyimak Siswa pada Pembelajaran Bahasa Indonesia Kelas V di Sekolah Dasar - Hamidah Farhani Rangkuti (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to find out whether there is an influence of audio-visual media on listening skills in class V Indonesian Language subjects at elementary school. This research has several problems, namely the low level of listening skills in Indonesian Language learning which is caused by a lack of maximizing learning methods and media as well as a lack of student involvement in the learning process. This research is a quasi-experimental quantitative. This research sample used Purposive Sampling Technique which consisted of two classes, namely class V A with 23 students as an experimental class using audio visual media and class V B with 23 students as a control class without using media. The data collection technique used in this research is a multiple choice test. The results of the research in the experimental class were with an average pretest score of 57.97 and an average posttest score of 83.19. From the t-test hypothesis, the value of tcount is 8.653 > ttable 1.679 at the significance level (α) = 0.05 and df (n1=n1) -2 = (23+23)-2= 44. This means that H1 is accepted and H0 is rejected. So, it can be concluded that there is an influence of audio-visual learning media on students' listening skills in class V Indonesian language learning at elementary school for the 2023/2024 academic year.